PENGARUH KEPEMIMPINAN, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PEGAWAI DINAS PERTANIAN TANAMAN PANGAN HORTIKULTURA DAN PETERNAKAN KABUPATEN PASAMAN BARAT - Rezi Wismora; Bustari Muchtar (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The aim study  is to analyze the influence of leadership, compensation and employee work motivation  in Department of agriculture and horticulture crops and Department of livestock West Pasaman. Sampling was taken  based on proportional stratified radom sampling. Analysis of data used path analysis and hypothesis testing using the f and t test. The result of this study indicate that (1) Leadership has a significant influence on employee work motivation in Department of Agriculture , horticulture crops and livestock West Pasaman (2)Compensation has a significant Influence Employee work motivation in Departement of agriculture, horticulture crops and livestock West Pasaman (3) Work environtment has a significant influence on employee work motivation in Department Agriculture, horticulture crops livestock West Pasaman. On employee work motivation. From this research, it appears that  the variable of leadership has a greater influence than the variable compensation and work motivation. Compensation is the smallest variable in this research. So it can be interpreted that variable of leadership has a very important influence in improving on employee work motivation in Department of Agriculture and horticulture crops and Department of livestock West Pasaman. Keywords: transfer, compensation, work motivation, job satisfaction.